HIV-related needs for safety among male-to-female transsexuals (mak nyah) in Malaysia - Yik Koon Teh (Taylor & Francis Group, 2008)
This research, commissioned by the Malaysian AIDS Council in 2007, is qualitative and descriptive in nature. In depth face-to-face interviews were carried out with 15 mak nyah respondents from five major towns. The interviews were guided by an interview schedule that had seven main topics: brief background; hormone-taking behaviour; safe sex; health care; substance abuse; harassment from authorities; and HIV prevention. The HIV problem among the mak nyah, mak nyah sex workers and their clients is critical. Many do not have in-depth HIV/AIDS knowledge and do not practise safe sex. The problem gets worse when most mak nyah do not consider HIV/AIDS as a primary concern because of other pressing problems like employment and discrimination. There are also no HIV prevention activities in many parts of Malaysia. Mak nyah also face constant harassment from enforcement authorities for prostitution. This hampers HIV prevention work.